Cracked tooth syndrome: a diagnostic dilemma- a mini review - Raj, Shreya; Singh, Ankita (Frontiers in Oral Health, 2025)
BackgroundCracked tooth syndrome is one of the five types of longitudinal fracture. It has been described as an incomplete fracture progressing from the vital tooth crown and progressing subgingivally, usually in a mesio-distal direction, involving dentin and often the dental pulp. Though termed as a syndrome it doesn't present with a set of classical symptoms. Hence, its diagnosis has always been arduous. This review paper summarises the current strategies in diagnosing a cracked tooth. This paper is an attempt to draw standardized protocols for diagnosing cracked tooth.ObjectiveThe objective of this paper is to delve deeper into cracked tooth syndrome, thereby examining and simplifying each method to elucidate better its representation in clinics, such as history, examination, imaging etc. for an easier diagnosis.Clinical significance and relevanceCracked tooth syndrome is a prevalent problem in dental practice. However, its ambiguous symptoms make a definitive diagnosis difficult, leading to a delay or failure to give appropriate therapy. Thus, it is imperative for a clinician to know about the various methods to correctly diagnose and provide apt and early treatment for cracked teeth.